Critical thinking: Its relevance for education in a shifting society - Almeida, Leandro da Silva (2011)
The amount of information and variety of situations tackled on a daily basis call for new cognitive functions, namely combining knowledge, experience and intellectual abilities. Critical thinking is valued as a higher-order type of reasoning and a skill transversal to the educational organisms. We introduce some definitions suggested in the literature, and describe the cognitive functions responsible for critical thinking used in learning and problem solving situations. We then present the most used assessment procedures, illustrating with instruments as well as programs and curricular planning implemented in the classroom to teach and develop critical thinking. Finally, we highlight the importance of further investigation, in order to reach a convergence of theoretical and practical elements needed to define critical thinking.